2019
DOI: 10.22190/fupes190612019v
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Tactical Analysis of Goal Scoring Patterns in the 2018 Fifa World Cup in Russia

Abstract: The aims of this research are to record and analyze the goals scored during the 64 matches in the 21st World Cup in Russia in 2018, to highlight those factors that are directly related to the teams' effectiveness in scoring, to record the goals approved after the use of new technologies, video assistant referee and goal line technology, as well as their effect on the outcome of the game. Chi-square and univariate general linear methods were used for the data analysis. Statistical difference is observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
6
13
0
Order By: Relevance
“…The results imply that more goals were scored in the second half than in the first half. This finding is in line with previous studies carried out in both national leagues [19] and international tournaments involving national teams [14,15,21,22]. The difference is also reflected in the 15-minute periods, where the periods of the second half presented higher frequencies of goals than those in the first half.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results imply that more goals were scored in the second half than in the first half. This finding is in line with previous studies carried out in both national leagues [19] and international tournaments involving national teams [14,15,21,22]. The difference is also reflected in the 15-minute periods, where the periods of the second half presented higher frequencies of goals than those in the first half.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the results showed that the team that scored the first goal gained significant advantage in winning the match, as it was indicated in 73.33% of the cases in which home teams scored first goals and in 59.6% of the cases in which visitor teams scored the first goal, eventually winning the match. A similar effect of the first goal on the match outcome has been reported in previous studies [8,11,14,15,22]. When a team scores the first goal, there is an improvement in performance and the players present more self-confidence and passion [30,31].…”
Section: Discussionsupporting
confidence: 73%
“…As for the starting zones of the goal-scoring attacks, it appears that the teams from both leagues in the sample scored most of their goals when their attacks were initiated mainly in the attacking zone, followed by those starting in the central zone and last from the defensive zone. As a result, the attacking third of the pitch appears to be the starting zone of the most successful attacks performed by top teams (similar results were recorded in the study by Vergonis et al, 2019), which could be due to the pressure applied by these teams on their opponents in this specific area in order to gain possession of the ball.…”
Section: Discussionsupporting
confidence: 76%
“…This trend of the advantage of scoring first was consistent with previous results on both international and national events. In international tournaments (including FIFA World Cup), scoring first helped teams win over 70% of their matches (Leite, 2015;Vergonis et al, 2019). In domestic leagues, scoring first also increased the probability of winning (71.43-86.15%; Armatas, et al, 2009a,b;Molinuevo and Bermejo, 2012;Lago-Peñas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, scoring first has a strong influence on match outcome (Bloomfield et al, 2005). Across worldwide football tournaments, scoring first has been shown to be an effective predictor of the final outcome in the 2018 FIFA (Fédération Internationale de Football Association) World Cup (71.40%; Vergonis et al, 2019), the six major football tournaments in the world (71.17%; Leite, 2015), the Greek league in the -2007Armatas et al, 2009bArmatas et al, ) and 2007Armatas et al, -2008Armatas et al, 2009a), and the La Liga (Spanish League) from the 2005 to 2010 seasons (79.32%; Molinuevo and Bermejo, 2012).…”
Section: Introductionmentioning
confidence: 99%